Theoretical Models in the Study of Temperature Effect on Steel Mechanical Properties - D. Gorbănescu; Ana-Diana Ancaş (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2006)
The governing laws adopted by two high qualified scientific organizations (D.T.U. and Eurocode) for the variation of steel mechanical properties at high temperatures are presented. There are no significant differences between them, but generally, the items advanced by Eurocode 3, part 1.2, are dopted in the most works that approach the thermical-mechanical analysis of steel structures.